Cerebral Hemodynamics on MR Perfusion Images before and after Bypass Surgery in Patients with Giant Intracranial Aneurysms - Caramia, Francesca; Santoro, Antonio; Pantano, Patrizia; Passacantilli, Emiliano; Guidetti, Giulio; Pierallini, Alberto; Fantozzi, Luigi Maria; Cantore, Gian Paolo; Bozzao, Luigi (American Journal of Neuroradiology, 2001)
BACKGROUND AND PURPOSE: Preoperative assessment of the anatomy and dynamics of cerebral circulation for patients with giant intracranial aneurysm can improve both outcome prediction and therapeutic approach. The aim of our study was to use perfusion MR imaging to evaluate cerebral hemodynamics in such patients before and after extraintracranial high-flow bypass surgery.METHODS: Five patients with a giant aneurysm of the intracranial internal carotid artery underwent MR studies before, 1 week after, and 1 month after high-flow bypass surgery. We performed MR and digital subtraction angiography, and conventional and functional MR sequences (diffusion and perfusion). Surgery consisted of middle cerebral artery (MCA)–internal carotid artery bypass with saphenous vein grafts (n = 4) or MCA–external carotid artery bypass (n = 1).RESULTS: In four patients, MR perfusion study showed impaired hemodynamics in the vascular territory supplied by the MCA of the aneurysm side, characterized by significantly reduced mean cerebral blood flow (CBF), whereas mean transit time (MTT) and regional cerebral blood volume (rCBV) were either preserved, reduced, or increased. After surgery, angiography showed good canalization of the bypass graft. MR perfusion data obtained after surgery showed improved cerebral hemodynamics in all cases, with a return of CBF index (CBFi), MTT, and rCBV to nearly normal values.CONCLUSION: Increased MTT with increased or preserved rCBV can be interpreted as a compensatory vasodilatory response to reduced perfusion pressure, presumably from compression and disturbed flow in the giant aneurysmal sac. When maximal vasodilation has occurred, however, the brain can no longer compensate for diminished perfusion by vasodilation, and rCBV and CBFi diminish. Bypass surgery improves hemodynamics, increasing perfusion pressure and, thus, CBFi. Perfusion MR imaging can be used to evaluate cerebral hemodynamics in patients with intracranial giant aneurysm.